2017
DOI: 10.4103/apjon.apjon_13_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of play-based occupational therapy on symptoms of hospitalized children with cancer: A single-subject study

Abstract: Objective:Cancer is one of the four leading causes of death in children. Its courses of diagnosis and treatment can cause physiologic symptoms and psychological distress that secondarily affect children's quality of life and participation in daily activities. The aim of this study was to investigate the effect of play-based occupational therapy on pain, anxiety, and fatigue in hospitalized children with cancer who were receiving chemotherapy.Methods:Two hospitalized children with acute lymphoblastic leukemia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 23 publications
0
12
0
4
Order By: Relevance
“…Studies have also reported that distracting play activities eff ectively reduce pain and fear during invasive procedures (17,21,35). It has also been shown that preoperative play activities reduce fear, anxiety, and pain levels (16,(36)(37)(38). Mohammadi et al (2017) reported that play activities eff ectively reduced the pain, anxiety, and fatigue levels of children hospitalized for chemotherapy (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also reported that distracting play activities eff ectively reduce pain and fear during invasive procedures (17,21,35). It has also been shown that preoperative play activities reduce fear, anxiety, and pain levels (16,(36)(37)(38). Mohammadi et al (2017) reported that play activities eff ectively reduced the pain, anxiety, and fatigue levels of children hospitalized for chemotherapy (16).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that preoperative play activities reduce fear, anxiety, and pain levels (16,(36)(37)(38). Mohammadi et al (2017) reported that play activities eff ectively reduced the pain, anxiety, and fatigue levels of children hospitalized for chemotherapy (16). Potasz et al (2013) found that children who participated in play activities in hospitals had lower cortisol levels in their urine (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persian version of this scale with a good reliability (r = 85%) has been used in various studies. [1718] And the third part was Zarit Caregiver Burden Scale (ZBS) for the mothers with 22 items scored on a scale ranging from 0 to 4 (never, rarely, sometimes, mostly, and always, respectively). A total score of 0, less than 30,30–60, 61–88, and 88 indicated no, slight, moderate, severe, and the highest caregiver burden, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…El juego facilita el desarrollo de procesos sensoriales, motores y cognitivos, por lo cual los niños enfermos necesitan jugar, tal vez incluso más que los niños sanos (Mohammadi et al, 2017;Stenman et al, 2019). Garantizar que los niños hospitalizados tengan la posibilidad de jugar resulta esencial, pues la imposibilidad de hacerlo a menudo conduce al desarrollo de patrones de comportamiento dependientes, impotencia aprendida y depresión (Weiss et al, 2003).…”
Section: Introductionunclassified